Analisis Efektivitas Penggunaan E-Filing dalam Penerimaan Pajak pada KPP Pratama Medan Barat - Simbolon, Deliyanti; Afrida, Fenny; Wahyuni, Putri (Journal of Management and Economics Research, 2024)
The purpose of knowing the use of E-filling at KPP Pratama Medan Barat and to determine the effectiveness of the use of E-filling in tax revenue at KPP Pratama Medan Barat. This research uses qualitative data from primary data sources and secondary data sources. This research used data collection techniques, namely interviews and documentation studies Location This research was conducted at the West Medan Pratama Tax Service Office located at Jl. Dormitory No. 7-A, Sei Sikambing C ll, Medan Helvetia, Medan City, North Sumatra 20123. Findings Based on the results of the study, it is known that the number of WPOPs who submit tax returns from the West Medan Sub-district using E-filling is already large and increases every year, thus showing the effectiveness of the use of E-filling in tax revenue at the KPP Pratama Medan Barat has reached the expected amount with an average percentage - 100% in the last 5 years. Implications In addition, every process of E-filling still has weaknesses, but with the socialisation that is often carried out by the West Medan KPP to individual taxpayers related to the use of e-filling, it increases the knowledge of individual taxpayers in its use so that it increases confidence in the use of e-filling and with this convenience it affects tax revenue at the West Medan KPP. And the hope is that the fiscus is always responsive to the difficulties experienced by taxpayers in using e-filling. This research approach is descriptive research that refers to inductive data analysis Research Type - Empirical Study / Field Study.